PROXIMATE CONTENT AND SENSORY ACCEPTABILITY OF CARROT AND SWEET POTATO – FILLED CHOCOLATE BITES INCORPORATED WITH LACTOBACILLUS CASEI AND LACTOBACILLUS PLANTARUM (Global Journal of Advanced Engineering Technologies and Sciences, 2016)
In this study, producing carrot and sweet potato-filled chocolate bites incorporated with probiotics including L. plantarum and L. casei was investigated for three weeks. The proximate content and sensory acceptability were determined. Results showed that the developed carrot and sweet potato-filled chocolate bites are high in ash, fat and moisture while they recorded low protein and carbohydrate contents after conducting proximate analysis. On the other hand, sensory analysis showed that carrot and sweet potato - filled chocolate bites during the study were generally acceptable. All sensory parameters showed no significant difference with each other. It can therefore be concluded that the carrot and sweet potato-filled chocolate bites are generally acceptable based on its proximate content and sensory acceptability.